Berberine alleviates atherosclerosis by modulating autophagy and inflammation through the RAGE-NF-κB pathway - Zhang, Peng; Jin, Meiying; Zhang, Lei; Cui, Yanjun; Dong, Xiaokang; Yang, Jie; Zhang, Jiayu; Wu, Haopeng (Frontiers in Pharmacology, 2025)
IntroductionLipid accumulation and foam cell formation are significant features that expedite the progression of atherosclerosis (AS). Abnormal autophagy is a key factor in the development of AS. The importance of berberine (BBR) in AS has been well established. However, its exact role in regulating autophagy and alleviating atherosclerotic inflammation remains unclear.PurposeThis study was aimed at exploring the role and mechanism of BBR in alleviating AS by activating autophagy and alleviating inflammation.Study designNetwork pharmacology predicts the potential mechanism of BBR in regulating AS and verifies this mechanism through in vivo and in vitro experiments, thereby providing new thinking for clinical treatment.MethodsThe potential mechanism through which BBR regulates AS was predicted by network pharmacology. Total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein (HDL-C) were measured by administering BBR (100 mg/kg) via the stomach. Hematoxylin and eosin (HE) and oil red O staining were used for histological analysis. Expression levels of the RAGE and p-NF-κB pathways and autophagy-associated proteins were evaluated by immunofluorescence. The ApoE−/− mouse model was established with a high-fat diet (HFD) to verify the effect and mechanism of BBR in vivo.ResultsFunctional and pathway enrichment analysis demonstrated that BBR significantly modulated the inflammation-related signaling pathways of AS. Additionally, in vivo experiments indicated that BBR reduced aortic lipid deposition and reduced the atherosclerotic plaque area. BBR decreased the expression levels of RAGE, p-NF-κB, TNF-α, and P62 in the aorta, and upregulated the expression levels of IL-10, CD31, VEGF, LC3B, and Beclin1. Similar results were obtained in vitro experiments, further supporting the in vivo findings. Notably, NF-κΒ activator 1 attenuated the effect of BBR.ConclusionIn summary, BBR alleviated the disease progression of AS by regulating the expression of RAGE and p-NF-κB and activating autophagy.